2013
DOI: 10.3732/apps.1200130
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effective microsatellite markers for Banksia integrifolia (Proteaceae)

Abstract: • Premise of the study: Microsatellite markers were developed to assess the level of genetic variation and population structure in Banksia integrifolia, a widespread species endemic to eastern Australia.• Methods and Results: We used next-generation sequencing approaches to identify and develop 11 polymorphic microsatellite markers with perfect tri- and tetranucleotide repeats. We tested these markers with 71 specimens from three populations. Observed and expected heterozygosities ranged from 0.0 to 0.875 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Genomic DNA was extracted from 30-mg tissue samples for individual specimens using the NucleoSpin ® 96 Plant II protocol (Macherey-Nagel Inc.), and DNA quantitation was performed as per the QuantiFluor ® dsDNA System (Promega Inc). Banksia marginata DNA samples were genotyped at 10 microsatellite loci using a composite of genetic markers developed by Lamont, 2008 andFatemi, Houliston, Haddadchi, &Gross, 2013, andadditional markers were developed in the present study using the approach outlined in Miller et al, 2019) (Table S2). In order to distinguish PCR products upon capillary separation, primers for the ten microsatellite markers were tagged with a unique fluorescent label during PCR using the method outlined in Blacket, Robin, Good, Lee, and Miller (2012).…”
Section: Dna Extraction and Genotypingmentioning
confidence: 99%
“…Genomic DNA was extracted from 30-mg tissue samples for individual specimens using the NucleoSpin ® 96 Plant II protocol (Macherey-Nagel Inc.), and DNA quantitation was performed as per the QuantiFluor ® dsDNA System (Promega Inc). Banksia marginata DNA samples were genotyped at 10 microsatellite loci using a composite of genetic markers developed by Lamont, 2008 andFatemi, Houliston, Haddadchi, &Gross, 2013, andadditional markers were developed in the present study using the approach outlined in Miller et al, 2019) (Table S2). In order to distinguish PCR products upon capillary separation, primers for the ten microsatellite markers were tagged with a unique fluorescent label during PCR using the method outlined in Blacket, Robin, Good, Lee, and Miller (2012).…”
Section: Dna Extraction and Genotypingmentioning
confidence: 99%
“…This is representative of much higher numbers of sequences that can be obtained using NGS in comparison to older more traditional sequencing methods and is in congruence with numbers reported for other studies using 454 sequencing for microsatellite development in plants (e.g. Csensics et al, 2010;Fatemi et al, 2013). Despite both species having similar sequencing statistics the number of perfect microsatellites detected that were suitable for primer design was considerably higher in A. stenophylla (893) than D. florulenta (354).…”
Section: Discussionsupporting
confidence: 86%
“…Each leaf was subsampled and genomic DNA extracted [44]. A subset of 16 samples from several of the remnants were used to test 30 microsatellite (SSR) primer pairs developed for other Banksia species [45][46][47][48][49][50] (Supplementary Table S1). Ten of these primer pairs either amplified poorly or failed to amplify and were eliminated.…”
Section: Dna Extraction and Genotypingmentioning
confidence: 99%
“…A further eight primer pairs amplified well but exhibited little to no polymorphism across the 16 samples and were also eliminated. The remaining twelve primer pairs were amplified across all samples but a review of the data generated revealed poor amplification of some loci in a small number of populations leaving eight primer pairs for analysis (BO22, Br3 and Br13 [45], Bint02, Bint07, Bint05 and Bint24 [47] and BH-B8 [46]). PCR (5µL) compris-ing of 1 X PCR buffer (Invitrogen, Grand Island, NE, USA), 2 mM MgCl 2 (Invitrogen), 0.2 mM of combined dNTPs (Sigma, Perth, Australia), 0.25 µM M13 tagged fluorescent primer (tagged with FAM from Thermo Scientific (Scoresby, Victoria, Australia) or NED, PET or VIC from Applied Biosystems (Mulgrave Australia)), 0.05 µM forward primer, 0.25 µM reverse primer, 10% BSA, 10% PVP-360, 5U/µL Platinum Taq (Invitrogen) and 25 ηg template DNA were amplified using an Eppendorf Mastercycler with a step down program as previously outlined [51].…”
Section: Dna Extraction and Genotypingmentioning
confidence: 99%